Intelligent data engineering and automated learning – IDEAL 2017 : 18th International Conference, Guilin, China, October 30-November 1, 2017, Proceedings /: 18th International Conference, Guilin, China, October 30-November 1, 2017, Proceedings. (2017) - Unknown
No abstract available